The impact of outreach programs on academics development, personal development and civic responsibilities of dental students in Bhubaneswar city - Vinay Suresan (Journal of Education and Health Promotion, 2019)
INTRODUCTION: Inequalities persists in distribution, accessibility, and utilization of oral health services between urban and rural population. One approach to lessen this inequality is by incorporating rural outreach programs in the academic curriculum of health-care professionals. OBJECTIVES: The objective of the study was to evaluate the effectiveness of outreach programs on academic development, personal development, and civic responsibilities of dental students and also to assess the changes in the domain scores within and between genders postintervention. METHODOLOGY: The study population consisted of 100 dental students. The study methodology followed a before and after without control informal experimental study designs. At baseline, the participants were administered pretested structured questionnaire developed by D. Diaz Gallegos. Intervention involved posting participants in various rural outreach activities and academic field visits in various public health installations. A postintervention questionnaire developed by Anu F. Shinnamon et al. was administered to assess the change from the baseline. The change in domain scores was assessed using paired and unpaired t-test appropriately. P≤ 0.05 was considered as statistically significant. RESULTS: The baseline scores of academic, personal, and civic domains were 6.05 ± 2.44, 8.04 ± 2.84, and 6.36 ± 2.23 which increased to 6.52 ± 2.10, 13.56 ± 3.44, and 8.55 ± 2.71 postintervention, respectively (P ≤ 0.05). When comparing within genders, there was increase from the baseline, and this change in the scores postintervention was statistically significant (P = 0.001). The mean scores of all three domains between genders were statistically insignificant. CONCLUSION: The outreach programs developed and enhanced the subject's academic skills, leadership qualities, self-confidence, communication skills, managerial skills, and responsibilities toward the rural community.